Is there a difference in how people from different socio-environmental contexts perceive discomfort due to glare from daylight?. (January 2022) - Pierson, C; Piderit, B; Iwata, T; Bodart, M; Wienold, J
Exposure to daylight has much to offer and should be optimised to maximise its potential. In order to harvest its benefits, any visual discomfort from daylight should be anticipated and minimised. Hence, there is the need to predict discomfort from daylight glare. While more than 20 models for predicting discomfort from daylight glare have been developed, none accurately predict it. The inclusion of additional factors in the models may improve the predictions. One such factor is the socio-environmental context of the observer. This study compares the evaluations of discomfort glare from daylight for office buildings in four socio-environmental contexts: Chile, Belgium, Japan and Switzerland. The evaluations of discomfort glare, each consisting of subjective assessments and physical measurements of a view condition, were collected at the office desks of 401 participants, although only 211 responses were used in the analyses due to exclusion rules. The results do not suggest evidence of an influence of socio-environmental context on discomfort from daylight glare. In other words, the participants in this study perceived discomfort glare similarly, regardless of their socio-environmental context.